The Effect of the Nonplastic Fines on the Cyclic Resistance of the Saturated Sand-Fines Mixtures - Ke Cheng (Advances in Materials Science and Engineering)
A series of undrained cyclic triaxial tests were carried out to study the nonplastic fines on the cyclic behaviour of saturated sand-fines mixtures. The influences of the fines content (FC), global void ratio (e), and relative density (Dr) were considered. The results show that the cyclic resistance ratio (CRR) of the mixtures firstly decreases and then increases, finally stabilizing with increasing FC when the samples are prepared at a constant Dr. The CRR reaches its minimum when the FC is 20%. However, the CRR decreases and then increases with increasing FC when the samples are prepared at a constant e. The CRR reaches its minimum when the FC is at 30%. The CRR of the mixtures increases with increasing Dr when the FC is given. A single Dr or e cannot describe the dense state of the mixture effectively. A new index, Dr/e, is proposed in this study to describe the dense state of the mixtures. A semiempirical model is proposed to evaluate the CRR of the mixtures using the parameters of Dr/e and FC of the mixture based on the back analysis method. The applicability of the model is verified by the test data from this study and other scholars. In addition, the parameters of Dr/e and FC of the mixture can be obtained from basic geotechnical tests, which is convenient for the application of the model.